Vpliv nekaterih ekoloških dejavnikov na pojavljanje gozdnega jereba Bonasa bonasia v Bohinju - Mihelič, Barbara (Zbornik gozdarstva in lesarstva, 2004)
The authors of the paper studied the influence of certain ecological factors on the appearance of Hazel Grouse Bonasa bonasia in eight study areas in Bohinj. The study areas included 143 census points on which 25 territorial males were recorded. Beside that, the authors collected 79 accidental observations of Hazel Grouse, which were included in the research. Hazel Grouse prefers higher altitudes. The main part of the population was found between 1280 and 1490 m above see level. The comparison between systematicallyand accidentally obtained data showed no differences. The presence of deciduous trees in a forest proved to have no influence on the occurrence of Hazel Grouse. Most sightings of Hazel Grouse were made in plots with a higher proportion of conifers, although these plots were no different from the other study areas. The appearance of Hazel Grouse depended mostly on the presence of forest openings around census points, but also on the canopy closure in the shrub and field layers. Hazel Grouse preferred census points with a higher canopy closure in the shrub and field layers as well as a higherproportion of forest openings. Most of the forest openings in the study area are a result of Alpine dairy pastures. Such pastures possess three important components of a Hazel Grouse habitat: an increasing proportion of forest openings and of the shrub and field layers in the forest.
Keywords: ekologija živali; gozdni jereb